CAPITALIZING ON LEAD IN STAGE TO NURTURE CRITICAL THINKING: AN ATTEMPT TO COMBAT FAKE NEWS FOR SCREENAGERS - Rini Silvana (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
The study aims at improving critical thinking skill of screenagers – students who frequently face their smartphone screens – to be more critical consumers of information in the Internet era. Technological advances have made the instantaneous access to information possible. However, valid information exists in the same context as the fake ones. The challenge now appears to be abilities to distinguish valid and fake information. Using a 10-minute critical thinking activities during the lead in stage as the action, the research explores how integrating critical thinking and problem solving in daily classroom activities help nurture students to be critical in the information coming to their social media accounts. To achieve the objectives, a classroom action research involving cycles of Planning, Acting, Observing, and Reflecting was conducted in an Islamic-based higher secondary school in Tangerang, Banten. This research utilized a teacher's journal, a questionnaire, and an interview guide for eliciting data. The data were analyzed descriptively and the results showed that students’ critical thinking skill improved from cycle 1 to cycle 2. Results from questionnaire showed that students could differentiate fact and opinion as well as analyze information on their screens. A focus-group interview supported students’ improvement on critical thinking skill highlighting that their ability to distinguish valid or fake information improved gradually. Innovative activities that involve teachers, students, and school policy makers with critical thinking skill improvement should be encouraged.